PERANCANGAN PERANGKAT LUNAK SISTEM INFORMASI PENDATAAN GURU DAN SEKOLAH (SINDARU) PADA DINAS PENDIDIKAN KOTA TANGERANG SELATAN - Maulana, Yana Iqbal (Jurnal Pilar Nusa Mandiri, 2017)
The development of technology in today's world influence and a great impact on the development of education information system. In the world of information systems there are many models of information systems aimed at providing various kinds of information, and with the progress of technology has developed very fast, it was marked by the increasing number of computer based information system, so that people can quickly to obtain the desired information, as well as a system of data collection on teacher and school information. One proposed solution to optimize data management and school teachers are implementing the Application System Data Collection Teacher And School (SINDARU). SINDARU is a computer-based information systems used to support teachers and school data collection system with the government agency South Tangerang City Department of Education.